Prehistoric man human evolution (Just the facts learning series., 2007)
"Viewers come face to face with fascinating ancient creatures who looked something like apes but walked upright. We learn how they lived in their foraging societies; what their life may have been like; how they fashioned tools out of stone, wood and bone; and how scientists determine the age of the fossils that give us windows to their world. Moreover, we examine patterns that developed, which give us insight into human adaptation and evolution."--Container.